Implementasi Kebijakan Wajib Belajar 12 Tahun Di Kabupaten Kolaka - Khairunnisa Khairunnisa; Agus Tinus (Universitas Muhammadiyah Malang, 2018)
Abstract: The purpose of this study is to describe 1) the implementation of the 12-year compulsory education policy in Kolaka Regency; 2) obstacles encountered in implementing the 12-years compulsory education policy in Kolaka Regency; 3) the efforts of schools and the government in overcoming problems encountered in the implementation of 12-year compulsory education in Kolaka Regency. The type of research used is descriptive qualitative. Informants in this study are: a) Secretary of the Kolaka Regency Education Office; b) head of the primary and secondary education division of Kolaka Regency; c) the principal; d) parents of students, and e) students. Data collection techniques are interviews, observation, and documentation. Stages of data analysis are data reduction, data presentation, and conclusions. To check the validity of the data using the triangulation of data and sources. Research result; 1) the implementation of the 12-year compulsory education policy in Kolaka Regency consists of 3 main elements, namely implementing the policy. the program, target group. 2) the constraints to implementing the 12-year compulsory education in Kolaka Regency are the lack of budget, zoning system, lack of parents' understanding of education and lack of children's interest in school, a weak economy, lack of facilities and infrastructure, lack of teachers in remote areas. 3) efforts made on the implementation of 12-year compulsory education namely the Department of Education prioritize the more important and urgent, schools accept according to the capacity of the class and students can register outside the zoning area, provide understanding to the community about the importance of education, conduct socialization to the community to participate free of charge and provide scholarships for underprivileged children, submit proposals for the procurement of facilities and infrastructure, appoint contract teachers to remote areas.Keywords: Policy, Implementation, Compulsory Education Abstrak:Tujuan dari penelitian ini adalah untuk mendeskripsikan 1) implementasi kebijakan wajib belajar 12 tahun di Kabupaten Kolaka; 2) kendala yang dihadapi dalam implementasi kebijakan wajib belajar 12 tahun di Kabupaten Kolaka; 3) upaya sekolah dan pemerintah dalam mengatasi masalah yang dihadapi dalam implementasi wajib belajar 12 tahun di Kabupaten Kolaka.Jenis penelitian yang digunakan adalah kualitatif deskriptif. Informan dalam penelitian ini yaitu: a) Sekretaris Dinas Pendidikan Kabupaten Kolaka; b) kepala bagian pendidikan dasar dan menengah Kabupaten Kolaka; c) kepala sekolah; d) orang tua siswa; dan e) siswa. Teknik pengumpulan data yaitu wawancara, observasi dan dokumentasi. Tahapan analisis data yaitu reduksi data, penyajian data dan kesimpulan. Untuk mengecek keabsahan data menggunakan triangulasi data dan sumber. Hasil penelitian; 1) implementasi kebijakan wajib belajar 12 tahun di Kabupaten Kolaka terdiri dari 3 unsur utama yaitupelaksana kebijakan. adanya program, sasaran kelompok. 2) kendala implementasi wajib belajar 12 tahun di Kabupaten Kolaka yaituminimnya anggaran, sistem zonasi, kurangnya pemahaman orang tua tentang pendidikan dan kurangnya minat anak untuk sekolah, ekonomi lemah, sarana dan prasarana yang kurang, kekurangan guru pada daerah terpencil. 3) upaya yang dilakukan pada implementasi wajib belajar 12 tahun yaitu Dinas Pendidikan memperioritaskan yang lebih penting dan mendesak, sekolah menerima sesuai dengan daya tampung kelas dan peserta didik boleh mendaftar di luar wilayah zonasi, memberikan pemahaman kepada masyarakat mengenai pentingnya pendidikan, melakukan sosialisasi kepada masyarakat agar ikut berpartisipasi tanpa dipungut biaya dan memberikan beasiswa bagi anak yang kurang mampu, mengajukan proposal pengadaan sarana dan prasarana, mengangkat guru kontrak pada daerah terpencil.Kata kunci: Kebijakan, Implementasi, Wajib Belajar